Efficacy and safety of lurasidone in adolescents and young adults with schizophrenia: A pooled post hoc analysis of double-blind, placebo-controlled 6-week studies. Issue 1 (10th May 2021) - Costamagna, Isabella; Calisti, Fabrizio; Cattaneo, Agnese; Hsu, Jay; Tocco, Michael; Pikalov, Andrei; Goldman, Robert
Abstract: Background: The aim of this pooled analysis was to evaluate the efficacy and safety of lurasidone in the treatment of an acute exacerbation of schizophrenia in adolescents and young adults. Methods: The six pooled studies in this analysis used similar study designs and outcome measures. Patients (aged 13–25 years) were randomized to 6 weeks of double-blind, placebo-controlled treatment with lurasidone in fixed doses of 40, 80, 120, or 160 mg. The primary efficacy endpoint was Week 6 change in the Positive and Negative Syndrome Scale (PANSS) total score; secondary efficacy endpoints included Week 6 change in the Clinical Global Impression–Severity scale. Results: The safety population consisted of 537 patients (mean age: 18.1 years); 82.6% of patients completed the studies. Treatment with lurasidone was significantly better than placebo at all doses ( p < 0.001) for change in the PANSS total score at Week 6. Placebo-adjusted PANSS scores ranged from −9.4 to −16.1 (effect sizes: 0.53–0.90), with effect sizes increasing at higher doses. For lurasidone (combined doses), three adverse events occurred with a frequency of ≥5% (nausea: 13.5%; somnolence: 12.1%; akathisia: 10.1%). At last observation carried forward (LOCF)-endpoint weight gain of ≥7% was similar for lurasidone versus placebo (3.6 vs. 4.7%). Minimal median changes were observed at endpoint in cholesterol, −2.0 mg/dL; triglycerides, 0.0 mg/dL; and glucose, 0.0 mg/dL. Conclusions: In adolescents and young adults with schizophrenia, treatment with lurasidone in doses of 40–160 mg/d was a safe, well-tolerated, and effective treatment. Short-term treatment with lurasidone was associated with minimal effects on weight and metabolic parameters.